Genetic variants of BMP15 and BMPR-IB genes and association with litter size in pig - SONG Yi-ping; ZENG Yong-qing; CHEN Wei; CHEN Qi-mei; QIAN Yuan (浙江大学学报. 农业与生命科学版)
Four hundred and eighty-one pigs including Laiwu Black, Lulai Black, Licha Black, Luyan White, New Yimeng Black, Yorkshire, Landrace and Duroc were selected to detect genetic variants of BMP15 and BMPR-IB genes by PCR-SSCP. The genetic effects of the two genes on litter size were analyzed by least squares method. The results showed that the polymorphic sites of both BMP15 and BMPR-IB genes were found in all populations tested. The genotype distribution, however, revealed great differences between Shandong local breeds and foreign pig breeds. The effects of genotypes on total number born (TNB) and number born alive (NBA) were significant (P <0.05). For BMP15 gene, in AA genotypic sows, the average TNB and NBA of foreign pig breeds were 1.20 and 1.64 more than that of Shandong local breeds, respectively (P<0.05); in CC genotypic sows, the average TNB and NBA of foreign pig breeds were 1.20 and 0.82 more than that of Shandong local breeds, respectively (P <0.05). For BMPR-IB gene, in Shandong local breeds, the average TNB and NBA of AA were 0.49 and 0.51 more than that of BB, respectively (P >0.05); while the average TNB and NBA of BB was 1.05 and 0.90 more than that of AA in the foreign pig breeds, respectively (P<0.05).